Presupposition between ancient pragmatics and Cognitive pragmatics - Bextyar Nuri Hamadamin; Sabah Rashid Oadir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The meaning of linguistic units in the speaker's mind of a language works on a set of mathematical logic principles. To interpret the meaning of a statement, the recipient makes various assumptions, eventually, one of these assumptions becomes the basis for interpreting the speaker's intention, and this mechanism of meaning interpretation is known in pragmatics as presupposition. Presupposition includes all the possibilities that arise for interpreting a statement by the recipient of the message. In cognitive pragmatics, this is linked to background knowledge, environmental partnerships, and many other factors. On the other hand, it treats the hypothetical interpretation of utterances through several semantic theories that are different from the mechanisms and discussions written about in ancient pragmatics. Therefore, in this research, we try to go deeper into the presupposition as a subject, and the importance of this discussion in Cognitive pragmatics.